Environmental variables determining the occurrence of Cladonia parasitica and Hertelidea botryosa, two boreal lichens confined to wood - Källén, Ingela (2015)
Biodiversity is essential for human well-being and it is defined as the genetic variation within species and the variety of species and ecosystems. Biodiversity provides several ecosystem services which are necessary for human beings but there are different threats towards the biodiversity. The biodiversity linked to the forest in Sweden are threatened, about 50 % of the red-listed species in Sweden are associated with forests. This is linked to the commercial exploitation of the boreal forest in Sweden which started 200 years ago. The forestry the last 50 years, with clear-cuts, have contributed to a fragmented forest landscape. A change from old-growth forest with more than one tree species, trees in all dimensions and different substrates of dead wood have been converted to mainly young dense forests with only one tree species per stand. These production forests are defined as a forest though they do not contain all the different habitats and niches which many species are dependent on. There is a lack of knowledge about different demands of forest species and this master thesis is a step towards filling this gap, and it gives advice about how forest management can secure stable populations of two boreal wood-dependent lichen species, Cladonia parasitica and Hertelidea botryosa. The occurrence of the two lichen species was surveyed as well as different environmental variables which could help explain lichen occurrence. The inventory was performed in the province of Hälsingland which is located in the middle part of Sweden where the dominating tree species are Scots’ pine Pinus sylvestris and Norway spruce Picea abies. 24 stands of 4 different stand categories were inventoried (nature reserves/voluntary set aside areas, >65 years old, 20-64 years old, 8-19 years old) and three different dead wood types were sampled; snags, stumps and logs of P. abies, “ordinary” P. sylvestris and resin-rich P. sylvestris. Within each stand a transect of 10x200 metres was established inside the transect where all wooden objects were measured. For the statistical analysis a generalized linear mixed model was used to determine the most important environmental variables for lichen occurrence probabilities, based on the explanatory variables. Both lichens were almost only found on dead, old, resin rich, hard wood of pine. Charred wood seems to be the best explanatory variable for occurrence of H. botryosa but it is also significant that the occurrence probabilities are higher in nature reserves/voluntary set aside areas compared with young stands and if the wood is exposed rather than shaded. Occurrence of C. parasitica seems to be best explained by stand category where nature reserves/voluntary set aside areas are preferred compared with other stand categories. Dead wood of resin rich pine is not created with the current dominating management of the forest and the areas of suitable nature reserves/voluntary set aside areas seem to be far too small to keep a viable population of the lichens in a long-term perspective. A forest management which creates connectivity between important habitats such as nature reserves, together with creation of suitable substrates (e.g. controlled forest fires to create resin rich pine wood), could help the two lichen species, and other species which are also dependent on this type of substrate. It is also important to for example, to protect the remaining old-growth forest which is not yet protected in order to increase the amount of suitable habitats.